The transcription factor ZmNAC49 reduces stomatal density and improves drought tolerance in maize. (1st November 2020) - Xiang, Yang; Sun, Xiujuan; Bian, Xiangli; Wei, Tianhui; Han, Tong; Yan, Jingwei; Zhang, Aying
Abstract : The transcription factor ZmNAC49 represses the expression of ZmMUTE and reduces stomatal density, leading to enhanced drought tolerance in maize. Abstract: Drought stress severely limits the growth, development, and productivity of crops, and therefore understanding the mechanisms by which plants respond to drought is crucial. In this study, we cloned a maize NAC transcription factor, ZmNAC49, and identified its function in response to drought stress. We found that ZmNAC49 is localized in the nucleus and has transcriptional activation activity. ZmNAC49 expression is rapidly and strongly induced by drought stress, and overexpression enhances stress tolerance in maize. Overexpression also significant decreases the transpiration rate, stomatal conductance, and stomatal density in maize. Detailed study showed that ZmNAC49 overexpression affects the expression of genes related to stomatal development, namely ZmTMM, ZmSDD1, ZmMUTE, and ZmFAMA . In addition, we found that ZmNAC49 can directly bind to the promoter of ZmMUTE and suppress its expression. Taken together, our results show that the transcription factor ZmNAC49 represses ZmMUTE expression, reduces stomatal density, and thereby enhances drought tolerance in maize.